Subsidizing the Stork: New Evidence on Tax Incentives and Fertility - Milligan, Kevin (The Review of Economics and Statistics, 2005)
This paper exploits the introduction of a pronatalist transfer policy in the Canadian province of Quebec that paid up to C$8,000 to families having a child. I implement a quasi-experimental strategy by forming treatment and control groups defined by time, jurisdiction, and family type. The incentive was available broadly, rather than to a narrow population as studied in previous work, providing an exceptional opportunity to investigate heterogeneous responses. I find a strong effect of the policy on fertility, and some evidence of a heterogeneous response that may help reconcile these results with previous estimates.